Reaksi Pasar Modal Terhadap Pengumuman Perombakan (Reshuffle) Terbatas Kabinet Indonesia Bersatu; Studi Empiris Pada Perusahaan Perusahaan yang Terdaftar di Bursa Efek Jakarta (BEJ) - C.Wahyu Estining Rahayu (Sinergi: Kajian Bisnis dan Manajemen, 2007)
This research analyzes capital market’ reaction to announcements of limited reshuffle of Indonesian Cabinet (Kabinet Indonesia Bersatu) in Jakarta Stock Exchange (JSX). The announcements is full of political events, that is information of joining Boediono in the cabinet (duet with Sri Mulyani Indrawati), which is being predicted to be able to solve nation’s economic problems today. This research hypothesizes that the capital market reacts positively to the announcements of limited reshuffle of Indonesian Cabinet (Kabinet Indonesia Bersatu).         A sample of 45 firms, which are included in LQ 45 category, are all fulfilling liquidity and market capitalization criteria. Research period consists of estimation period and event period, from September 30th, 2005 until December 19th, 2005. An event study technique is employed to analyze capital market’ reaction to announcements of limited reshuffle.         The study documented that there is a significant positive abnormal return (used as a proxy of  capital market’ reaction) surrounding the announcement date, which is before and after the announcements of limited reshuffle. The positive capital market’ reaction deal with signaling theory, that is the announcements of limited reshuffle tend to be articulated as a  signal of belief’ shareholders to SBY – JK performance (which is representated by the new economic team, between Boediono, as a Economic Coordinator Minister and Sri Mulyani Indrawati, as a Financial Minister) today and the future.Key words: abnormal return, limited reshuffle announcement, reaksi pasar modal